The impact of climate change on skin cancer incidence: mechanisms, vulnerabilities, and mitigation strategies - Wang, Lin; Chi, Yuan; Li, Jing; Yuan, Xingxing (Frontiers in Public Health, 2025)
Climate change is increasingly recognized as a major public health challenge with wide-ranging effects on health conditions, including skin cancer. Rising global temperatures and heightened ultraviolet (UV) radiation intensity due to ozone depletion are contributing to a significant increase in skin cancer cases worldwide. This review explores the impact of altered UV radiation levels, behavioral shifts, and environmental factors on vulnerable populations in relation to the connection between climate change and rising skin cancer incidence. This relationship is further complicated by several paradoxes involving human behavior, ozone layer recovery, and socioeconomic factors. The discussion focuses on the mechanisms linking climate change to higher skin cancer rates, particularly the roles of UV radiation exposure, increased temperatures, and ozone layer depletion. These environmental changes disproportionately affect vulnerable groups, such as children, the older adults, and populations in high-risk geographic regions. To mitigate the growing burden of skin cancer associated with climate change, public health strategies including sun safety education, early detection programs, and international climate policies must be prioritized. Predicting skin cancer incidence rates depends on current and past sun protection behaviors and preventive measures. This review underscores the need for a coordinated global response to climate change and its impact on skin cancer, emphasizing prevention, early diagnosis, and effective treatment.